Appren-tissages avec des papillons Monarques (Danaus plexippus). Une lecture d’« Histoires de Camille » de Donna Haraway - Laura Aristizabal Arango (Itinéraires)
This paper explores the articulation between multispecies kinship and knowledge production in Donna Haraway’s SF narrative “The Camille Stories” (2016). I focus on the stories of Camille 1 and Camille 2. I read these stories with tools of “Situated Knowledges”, Haraway’s well-known intervention in feminist standpoint epistemology, as well as those of Making Kin Not Population, a collective book co-edited by Adele E. Clarke and Haraway. After situating the Camille stories in the Chthulucene proposal, the paper highlights the epistemological dimension of Haraway’s slogan “make kin not babies”. Making kin engages Camille 1 and 2 in an embodied learning process. I explore the modalities of this embodiment in Haraway’s staging of characters that rebel against anthropocentrism – human-butterfly bodies. On this basis, I insist on the emergence of new sensibilities as a crucial dimension of attempts to partially repair damaged worlds.